Pengawasan Perdagangan Ilegal Terhadap Trenggiling oleh Balai Konservasi Sumber Daya Alam Sumatera Barat - Aulia Khairi, Fidela; Syofiarti, Syofiarti; Andora, Hengki (LPPM Universitas Ekasakti Padang, 2024)
The Natural Resources Conservation Agency (BKSDA) has one function, namely monitoring the illegal trade in wild animals, especially protected wild animals. The implementation of monitoring of illegal trade in protected wild animals by the West Sumatra BKSDA aims to protect protected wild animals from the danger of extinction and prevent trade in protected animals. However, the implementation of this function has not gone well, judging from temporary observation data showing that there is still a lot of trade in protected wild animals, especially pangolins. So, based on this, the author is interested in conducting research with the title Monitoring the Illegal Trade in Pangolins by the West Sumatra Natural Resources Conservation Agency (BKSDA).